Key-Point Based Copy-Move Forgery Detection and Their Hybrid Methods: A Review - Kaur, Harpreet; Saxena, Jyoti; Singh, Sukhjinder (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
Copy-move image forgery is one of the tampering techniques that need to be tackled with. Many copy-move forgery detection techniques such as exhaustive search, block and key-point matching based methods have been proposed for the detection of copy-move image forgery. Although key-point based methods were found better than block based methods in terms of computational efficiency, space complexity and robustness against rotation and scaling. However, key-point based methods also possess a number of limitations. So, researchers have proposed many integrated methods to cope up with the limitations of key-point based methods and to make copy move forgery detection more reliable. In this paper, keypoint based methods such as SIFT, SURF, ORB and their integrated methods are reviewed.